2006
DOI: 10.1111/j.1365-2621.2006.tb08928.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shelf Life of Superchilled Cod (Gadus morhua) Fillets and the Influence of Temperature Fluctuations During Storage on Microbial and Chemical Quality Indicators

Abstract: RISTBERGSSONRISTBERGSSON RISTBERGSSON steadily under superchilling conditions reaching counts as high as 7.6 log CFU/g at sensory rejection. steadily under superchilling conditions reaching counts as high as 7.6 log CFU/g at sensory rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 31 publications
11
88
1
Order By: Relevance
“…Those authors concluded that TVB-N and TMA-N can be controlled under the acceptable values within 21 days. Similar findings were reported by Olafsdottir [46] for super chilled cod (Gadus morhua) fillets storied 15 d at -1.5°C; Liu [39] for common carp (Cyprinus carpio) surimi processed with cryoprotectants (a mixture of sucrose and sorbitol) super chilled at -3°C; and Zhu [47] for catfish (Clarias gariepinus) fillets stored at -0.7°C under different packaging atmospheres: air (AP), vacuum (VP), and 60% CO 2 /40% N 2 (MAP) ( Table 1).…”
Section: Total Volatile Base Nitrogensupporting
confidence: 81%
“…Those authors concluded that TVB-N and TMA-N can be controlled under the acceptable values within 21 days. Similar findings were reported by Olafsdottir [46] for super chilled cod (Gadus morhua) fillets storied 15 d at -1.5°C; Liu [39] for common carp (Cyprinus carpio) surimi processed with cryoprotectants (a mixture of sucrose and sorbitol) super chilled at -3°C; and Zhu [47] for catfish (Clarias gariepinus) fillets stored at -0.7°C under different packaging atmospheres: air (AP), vacuum (VP), and 60% CO 2 /40% N 2 (MAP) ( Table 1).…”
Section: Total Volatile Base Nitrogensupporting
confidence: 81%
“…However, GC-MS analysis may provide data on volatile compounds that change with ageing as well as quantify the appearance of new (perhaps undesirable) aromatic notes previously determined by GC-O. [3] Looking for alternative methodologies, electronic noses (e-nose) can be a useful tool for a rapid characterization and discrimination of products, and they have been applied in shelf-life studies of different food products, such as tomato, [4] mandarins, [5] nuts, [6] apples, [7] bread, [8] cod fillets, [9] milk [10] and cheese, [11,12] among others.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, e-noses based on selective detection of the important volatile compounds, which are contributing to the spoilage odour (i.e. amines, sulphur compounds, alcohols, aldehydes, and esters) could be used to rapidly determine quality changes in fish [52].…”
Section: Smell-related Qualitymentioning
confidence: 99%